Answer:
![\bold{(x-2)^2+(y-3)^2=(1)/(4)}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/erpvtk1uiyuiumtyh78nyham3igu426bfx.png)
Center = (2, 3) radius =
![\bold{(1)/(2)}](https://img.qammunity.org/2020/formulas/mathematics/high-school/jzsjoeuhd3jm9ecx0berii5ag8yi1ixhoh.png)
Explanation:
When both the x² and y² values are equal and positive, the shape is a circle. Complete the square to put the equation in format:
(x-h)² + (y-k)² = r² where
- (h, k) is the vertex
- r is the radius
1) Group the x's and y's together and move the number to the right side
4x² - 16x + 4y² - 24y = -51
2) Factor out the 4 from the x² and y²
4(x² - 4x ) + 4(y² - 6y ) = -51
3) Complete the square (divide the x and y value by 2 and square it)
![4[x^2-4x+\bigg((-4)/(2)\bigg)^2]+4[y^2-6y+\bigg((-6)/(2)\bigg)^2]=-51+4\bigg((-4)/(2)\bigg)^2+4\bigg((-6)/(2)\bigg)^2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/8g8atfuz7qst3c51r9y2yh15qcy694u7fq.png)
= 4(x - 2)² + 4(y - 3)² = -51 + 4(-2)² + 4(-3)²
= 4(x - 2)² + 4(y - 3)² = -51 + 4(4) + 4(9)
= 4(x - 2)² + 4(y - 3)² = -51 + 16 + 36
= 4(x - 2)² + 4(y - 3)² = 1
4) Divide both sides by 4
![(x-2)^2+(y-3)^2=(1)/(4)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/mtplxphf3ja5pxd5w1ary3bu1yjhbay129.png)
- (h, k) = (2, 3)
![r=(1)/(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/5trdfqlsfhto3anbfctq6mmtehk20pcal6.png)